Triple Therapy with High‐Dose Proton‐Pump Inhibitor, Amoxicillin, and Doxycycline Is Useless for Helicobacter pylori Eradication: A Proof‐of‐Concept Study. Issue 2 (10th February 2014) - Almeida, Nuno; Romãozinho, José M.; Donato, Maria M.; Luxo, Cristina; Cardoso, Olga; Cipriano, Maria A.; Marinho, Carol; Sofia, Carlos
Abstract Introduction Helicobacter pylori resistance to antibiotics is steadily increasing and multidrug‐resistant strains are common and difficult to eliminate, mainly in countries where bismuth, tetracycline, furazolidone, and rifabutin are unavailable. Aim To evaluate the efficacy and safety of a triple therapy with proton‐pump inhibitor (PPI), amoxicillin, and doxycycline in patients with multidrug‐resistant H. pylori. Patients and Methods This prospective study involved 16 patients (13 females; mean age – 50 ± 11.3 years) infected by H. pylori with known resistance to clarithromycin, metronidazole, and levofloxacin, but susceptibility to amoxicillin and tetracycline. All patients were previously submitted to upper endoscopy with gastric biopsies for H. pylori culture and susceptibility testing by Etest. Mutations in 23S rRNA and gyrA genes were determined by real‐time PCR. A 10‐day eradication regimen with PPI (double‐standard dose b.i.d.), amoxicillin (1000 mg b.i.d.), and doxycycline (100 mg b.i.d.) was prescribed after pretreatment with PPI during 3 days. Eradication success was assessed by 13C‐urea breath test 6–10 weeks after treatment. Compliance and adverse events were determined through phone contact immediately after treatment and specific written questionnaires. Results Only one patient did not complete treatment due to adverse events. Another four patients experienced mild side effects not affecting compliance. The control 13C‐urea breath test was positive in all patients. Per‐protocol and intention‐to‐treat eradication rates were 0%. Conclusions Although safe, a triple‐therapy protocol with high‐dose PPI, amoxicillin, and doxycycline is useless for multidrug‐resistant H. pylori eradication.